Science to Unlock Climate Investments - CGIAR Research Initiative on Livestock and Climate; International Livestock Research Institute (International Livestock Research Institute, 2025)
The CGIAR Research Initiative on Livestock and Climate aimed to address livestock system climate adaptation and mitigation through five interrelated work packages. This series of Work Package Results Fact Sheets details our key outcome results. Livestock and Climate initiative’s Work Package 4 (WP4) responds to the critical challenge of increasing support for resilient and low-emission livestock systems by supporting public and private sector support in livestock by designing and tracking livestock investments that contribute to climate mitigation and adaptation, leveraging research-driven innovations and strategic partnerships. Our work focused on identifying priority regions, strengthening the business case for climate action in livestock systems and improving tools for measuring and verifying climate outcomes. WP4 operated globally, emphasizing regions and countries where the initiative was active, including Sub-Saharan Africa and Latin America. The initiative engaged primarily with investors to ensure financial flows into livestock systems sustainability and resilience.